Germany and the Baltic problem after the Cold War : the development of a new Ostpolitik, 1989-2000 - Spohr Readman, Kristina (Routledge, 2004)
The root question this book addresses is how the new Germany will use its re-found status as a great power. In seeking an answer, Kristina Spohr Readman scrutinises Germany's new Ostpolitik (eastern policy) in the period 1989-2000.
Keywords: Post-communism -- Baltic States.; Post-communism -- Europe, Eastern.; Germany -- Foreign relations -- Baltic States.; Baltic States -- Foreign relations -- Germany.; Germany -- Foreign relations -- Europe, Eastern.; Europe, Eastern -- Foreign relations -- Germany.; Postcommunisme -- Pays baltes.; Postcommunisme -- Europe de l'Est.; Allemagne -- Relations extérieures -- Pays baltes.; Pays baltes -- Relations extérieures -- Allemagne.; Allemagne -- Relations extérieures -- Europe de l'Est.; Europe de l'Est -- Relations extérieures -- Allemagne.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; Diplomatic relations; Post-communism; Baltic States; Eastern Europe; Germany